Rapid local adaptation mediates zooplankton community assembly in experimental mesocosms. (6th August 2015) - Pantel, Jelena H.; Duvivier, Cathy; Meester, Luc De; Vellend, Mark
Abstract Adaptive evolution can occur over similar timescales as ecological processes such as community assembly, but its particular effects on community assembly and structure and their magnitude are poorly understood. In experimental evolution trials, Daphnia magna were exposed to varying environments (presence and absence of fish and artificial macrophytes) for 2 months. Then, in a common gardening experiment, we compared zooplankton community composition when either experimentally adapted or D. magna from the original population were present. Local adaptation of D. magna significantly altered zooplankton community composition, leading to a suppression of abundances for some zooplankton taxa and facilitation for others. The effect size of D. magna adaptation was similar to that of adding fish or macrophytes to mesocosms, two important drivers of zooplankton community structure. Our results suggest that substantial amounts of variation in community composition in natural systems may be unexplained if evolutionary dynamics are ignored.